Avian Pathogenic Escherichia coli (APEC) in Broiler Breeders: An Overview - Jiddu Joseph; Li Zhang; Pratima Adhikari; Jeffrey D. Evans; Reshma Ramachandran (Pathogens, 2023)
Poultry meat is one of the major animal protein sources necessary to meet the global protein demand. Sustainability in broiler production is the key to achieving its continuous supply, and broiler breeders play a critical role in maintaining this sustainability by providing good quality chicks. Colibacillosis, the disease caused by avian pathogenic Escherichia coli (APEC), causes severe economic losses to the poultry industry globally. Moreover, APEC causes an additional burden among broiler breeders, such as a decrease in egg production and mortality among these birds. There is vertical transmission of APEC to the broiler chicks through eggs, resulting in increased first-week mortality and subsequent horizontal transmission at the hatchery. In this regard, the vertical transmission of antibiotic resistance genes is another concern that needs attention. Controlling several diseases in broiler breeders would possibly reduce the first-week mortality in chicks, thereby maintaining the production level. For that, constant monitoring of the bacterial populations is critical. Moreover, amidst the increased antibiotic resistance pattern, more focus on alternative treatment strategies like vaccines, probiotics, and bacteriophages is necessary. Future research focusing on strategies to mitigate APEC in broiler breeders would be one of the finest solutions for sustainable broiler production.